Xiānqǐ pī Lín pī Kǒng de xīn gāocháo
Cultural revolution-era female Chinese youth with raised fist and wooden baton with masses, red banners, and digging vehicles behind her Original title: 掀起批林批孔的新高潮 PO-1091